Does Foreign Aid Really Work? An Updated Assessment - and Riddell, Roger C. (Social Science Research Network, 2014)
This paper draws widely from the book Does foreign aid really work?, building on that discussion to provide an updated answer to the question based on recent evidence and contemporary debates on aid effectiveness. It starts with a brief discussion (Section 2) of the question: ‘does emergency aid work?’ This is important to the wider debate for two linked reasons. Firstly, the harshest critics of development aid are all supportive of emergency aid, with a number calling for its expansion in spite of evidence of major weaknesses and failures. Secondly, the sharp historical distinction made between emergency and development aid is becoming increasingly strained, as more emergency aid is being used a year or more after emergencies strike to rebuild lives and restore livelihoods, while more development aid is used to directly save lives.The rest of the paper focuses exclusively on development aid. Section 3 provides a rapid overview of the evidence of the impact of individual aid projects, including those of Non-Governmental Organisations (NGOs). The picture is overwhelmingly positive: well over 75% of projects meet their immediate objectives and impact has improved, even though sustaining benefits remains a challenge and there continue to be aid failures. Section 4 reviews the evidence of the wider and long-term impact of aid at the sectoral and country level, including a brief discussion of academic studies on aid and growth. Though there are still major gaps in our knowledge, the quality of the data is improving. However, there is little firm, quantitative evidence to show the specific contribution that aid has made to help achieve the Millennium Development Goals (MDGs), which are a central purpose of many current donor programmes (Section 4.2). More widely, there is plenty of evidence to suggest that aid has contributed positively to both growth and wider development at the sector and country level, though some studies suggest aid has had little or no impact. Overall, the contribution that aid makes to aggregate development is lower than the public has been led to believe (Sections 4.1, 4.3. and 4.4). Assessments of the overall impact of the aid provided by NGOs are rare, but a recent study suggests it has been positive (Section 4.5). More attention is now given to the issues of corruption in aid. Although there is evidence of aid funds being used for corrupt purposes and of aid worsening corruption, on balance it remains a minor issue. Aid has had significant successes in helping the poor affected by corruption (Section 4.6). The second half of the paper shifts focus to the large gap between what aid has done and what it might do. Section 5 discusses a range of inefficiencies within and across the aid system and their costs in terms of reduced impact, including the way aid is allocated, its growing complexity, and the volatility and unpredictability of aid flows (Section 5.1 and 5.2). These inefficiencies place in a different light the evidence of aid’s overall positive impact. The paper looks at the different initiatives that have been mounted to begin to address these weaknesses and failures, including the 2005 Paris Declaration, and discusses why donors have failed to honour the promises they have made to change the ways that they give aid.In Section 5.3, the paper argues that the most critical debate about whether aid works concerns the assessment of whether the short-term, immediate and extensive benefits that aid undoubtedly brings are outweighed by the direct and indirect systemic problems that it risks creating or accentuating. As increasingly over the last decade donors have channelled more of their aid into short-term, quick-impact projects, assessing the wider negative systemic effects of aid has become even more important. Some recent studies suggest that aid’s systemic problems are large and growing, narrowing the gap between aid’s harshest critics and broader analyses of aid impact. Against the backdrop of already too many proposals of how to make aid work better, Section 6 lays out nine concrete proposals for doing this: deepening knowledge of local contexts; ensuring short-term uses of aid are consistent with and supportive of long-term development, and that all aid is more closely related to overall recipient development goals and processes; helping build local capacities for recipients to be able to coordinate aid better; moving from rhetoric to reality in learning lessons from aid; using aid to help the poor in middle income countries; reducing volatility in aid at the country level; encouraging budget support by addressing donor-country political concerns; and rethinking ways of communicating about aid. Section 7 concludes. It suggests that, paradoxically, aid’s impact may well have been harmed by focussing too narrowly on trying to make short-term aid work better, and that the main focus of attention needs to widen to assess how aid can contribute more to a recipient’s own development goals. Additionally, donors need to help build the capacity of developing countries and developing country scholars to enable them to play a bigger role in helping to answer the question of whether aid works; unsettling though their assessments may be.